Anterior Hip Dislocation in a Football Player: A Case Report - Alexander Schuh; Sylvia Doleschal; Thomas Schmickal (Case Reports in Medicine)
Hip dislocations during sporting activities represent only 2%–5% of all hip dislocations. Most hip dislocations in sports can be categorised as “less complicated traumatic hip dislocations” by the Stewart-Milford classification due to the fact that minimal force is involved. The incidence of avascular necrosis of the femoral head greatly increases if the time to reduction is more than six hours. We report the case of a 38-year-old football player who suffered hip dislocation while kicking the ball with the medial aspect of the right foot in an external rotated manner of the right hip. Closed reduction was performed within 2 hours; postoperative follow-up was uneventful. Six months later the patient is out of any complaints; there is no sign of AVN of the femoral head.